Two Wars in the Order of Time: Cyprus, 1974, Ukraine, 2022 - Saldanha-Álvarez, José Maurício (Advances in Social Sciences Research Journal, 2023)
Two cases are studied, the first being the invasion of Cyprus by Turkey in 1974, when the Greek-Cypriot community wanted to integrate the island into mainland Greece, threatening the rise of Turkish Cypriots. The government of Turkey invaded the island, conquering a portion of the territory for its supporters, believing to resolve the issue culminating in decades of conflict between their communities whose past dreams do not coincide with the present. The second event is Vladimir Putin’s Russian invasion of Ukraine in 2022, motivated by the irreversible process of the dissolution of the former USSR and the attraction of Ukrainians to the western orbit. From a notion of the strangeness of contemporaneity, anchored in a glorious but unattainable past, events that erupt in contemporaneity are simultaneously current and anachronistic. Based on a premise of the past and defending ethnic Russians, Putin recovers the fantasy of a Russian empire encompassing tsarist, communist, and orthodox religions from the past. In Cyprus, Greek and Turkish Cypriots dreamed of integration into the motherland, but in both cases, contemporary and ancient irruption possess the unbeatable force of a cosmic event.